2009
DOI: 10.1093/carcin/bgp158
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 increases metastasis and immune escape of stomach cancer via the downregulation of CD70 and maintenance of CD44

Abstract: Cancer cells metastasize to the other site after escaping from the immune system and CD70, CD44 and vascular endothelial growth factor (VEGF) play important roles in this process. It is recently reported that interleukin (IL)-18 is closely related with the pathogenesis of skin tumor. Therefore, we investigated the role of endogenous IL-18 from stomach cancer on the immune escape mechanism and metastasis via the regulation of CD70, CD44 and VEGF expression. IL-18 and IL-18R expressions were not only investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 41 publications
4
57
2
Order By: Relevance
“…A previous study showed that IL18 directly increased the migration of gastric cancer cells through F-actin polymerization and decreased tensin levels (16). IL18 enhanced melanoma cell migration via the generation of reactive oxygen intermediates and the MAPK pathway (12), and IL18 might facilitate stomach cancer cell immune escape by suppressing CD70 and increasing metastatic ability by increasing CD44 and VEGF (15). We verified these mechanisms and confirmed that IL18 promotes tumor cell proliferation and invasion Figure 6.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A previous study showed that IL18 directly increased the migration of gastric cancer cells through F-actin polymerization and decreased tensin levels (16). IL18 enhanced melanoma cell migration via the generation of reactive oxygen intermediates and the MAPK pathway (12), and IL18 might facilitate stomach cancer cell immune escape by suppressing CD70 and increasing metastatic ability by increasing CD44 and VEGF (15). We verified these mechanisms and confirmed that IL18 promotes tumor cell proliferation and invasion Figure 6.…”
Section: Discussionsupporting
confidence: 70%
“…IL18 secreted by microglia (which had been activated by C6 gliomaderived extracellular matrix) enhanced migration of C6 glioma (14). Endogenous IL18 was shown to facilitate gastric cancer cell immune escape by suppressing CD70 and increasing gastric cancer cell metastatic ability by upregulating CD44 and VEGF (15). IL18 also increased cell migration directly through filamentous actin (F-actin) polymerization and tensin downregulation in gastric cancer cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these results suggest that IL-18 plays a key role in TSP-1 expression involving JNK (Kim et al, 2006). Endogenous IL-18 facilitate cancer cell immune escape by suppressing CD70 and increasing metastatic ability by upregulating CD44 and VEGF (Kang et al, 2009). IL-18 show dual effects on inhibition HBV replication and promotion of metastasis and migration in human hepatocytes.…”
Section: Role Of Il-18 In Immune Evasuionmentioning
confidence: 73%
“…IL-18 levels suppress CD70 expression and increases immune susceptibility of cancer cells. Endogenous IL-18 facilitate cancer cell immune escape by suppressing CD70 and increasing metastatic ability by upregulating CD44 and VEGF (Kang et al, 2009). Expression of IL-18/IL-18R were remarkably up regulates and triggered signaling pathway related to metastasis in hepatocellular carcinoma (Zang et al, 2011).…”
Section: Role Of Il-18 In Cancer Metastasismentioning
confidence: 99%
“…This cytokine appears to have both pro-and anti-tumor activities. On the one hand, IL-18 facilitated tumor cell immune escape by suppressing CD70, increasing metastatic potential, and promoting angiogenesis by stimulating production of CD44 and VEGF (52). On the other hand, IL-18 exerted antitumor effects by inducing an immune response to cancer cells, notably in colon cancer (20,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%